Les Épigrammes de Palladas d’Alexandrie (9. 173, 9. 489, 6. 85) et la tradition scolaire de l’Antiquité - Kondakova, Daria (Hyperboreus, 2016)
The paper deals with three epigrams written by Palladas of Alexandria, namely 9. 173, 9. 489 and 6. 85, that contain allusions to the ancient grammar tradition. It shows the results of an approach to their interpretation that is based on the analysis of this tradition and can shed some light on the explanation of especially difﬁcult epigrams of Palladas. In the epigram 9. 173, as we try to show, Palladas alludes to the fact that the ﬁrst ﬁve lines of the Iliad contain all the ﬁve grammatical cases. To understand correctly 9. 489, one should bear in mind that since Apollonius Dyscolus παιδίον is used as a standard example of a neutrum that does not correspond to the sex of person denoted. The epigram 6. 85 is a sophisticated play with grammatical concepts of syncope and apocope that is reinforced by its metrical structure (a three-word pentameter). We also suggest a new explanation of the name Γορδιοπριλάριος considering it as a syncope of Γορδιο(τειχίτης) πρι(μιπι)λάριος.